Pendampingan Operasionalisasi Sistem Informasi Manajemen (SIM) Pada BUMDA Desa Serangan - Putu Atim Purwaningrat; Rai Dwi Andayani W; Luh Nik Oktarini (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Management information system is an integrated human or machine system to provide information to support operations, management, and decision-making functions within an organization. Information and Communication Technology (ICT) is growing in tandem with science and the development of human civilization. The era of globalization seems so real with the ease of digital access in various parts of the world. The problems that occur at this time in the BUMDA of Serangan Village are still using manual records to process transactions for their business entities, of course this cannot be processed perfectly on current transactions so that they have difficulty in making decisions quickly. Traditional Village Owned Enterprises (BUMDA) have the task of maintaining village assets and managing them so as to provide additional income for the village. The purpose of this community service is to provide assistance in the BUMDA of Serangan Village to process data for every transaction made using computer technology to accelerate decision making.